Analysis of the Influence of Different Drying Methods on the Active Ingredients of Fresh Medicine - Yang, Jianqin; Miao, Mingsan (Chinese medicine and natural products, 2022)
The heating area of the material is large and the thermal efficiency is high, but it is necessary to control the suitable drying temperature of different medicinal materials to preserve the effective ingredients. Different kinds of Chinese medicine need different drying conditions to fulfill good drying requirements. Natural drying in the shade is one of the traditional drying methods, which takes a long time and is easily affected by the weather. The water volatilizes slowly. It is prone to mildew and discoloration during the drying process. However, it can better preserve the volatile oil components of Chinese medicine. The hot-air drying machine has lower requirements. The medicinal materials have a large heating area and high thermal efficiency, but it is necessary to control the appropriate drying temperature of different medicinal materials in order to preserve the active ingredients of the medicinal materials; it is not suitable for medicinal materials that stick and bind easily. The microwave drying method possesses superiority in drying some valuable medicinal materials such as Renshen (Radix et Rhizoma Ginseng) and Lurong (Cornu Cervi Pantotrichum), and the effective ingredients are preserved at a high degree; it can also achieve the purpose of killing enzymes and protecting glycosides and have a good bactericidal effect, but it is not suitable for Chinese medicines containing heat-sensitive ingredients, because it will destroy most of the proteins, amino acids, and peptides of Chinese medicine and result in the loss of efficacy. The far-infrared drying method is suitable for drying thin-layer medicinal materials and is friendly to the environment. Freeze-drying can preserve the active ingredients very well and greatly retain the efficacy, but it has obvious limitations in preserving some Chinese medicinal materials that need to kill enzymes and protect glycosides; besides, the cost is relatively high and the drying time is long.
Keywords: fresh medicine; drying method; natural drying; hot-air drying; microwave drying; far-infrared drying; freeze-drying